Breathing exercises with PEEP: efficiency and duration for correcting the cardiovascular system functional state in older patients with COPD - Asanov, E. O.; Holubova, Yu. I.; Dyba, I. A.; Asanova, S. O. (Zaporozhye Medical Journal, 2021)
The aim of the work is to find out the effectiveness and duration of the breathing exercises with PEEP action on the cardiovascular system state in older patients with COPD. Materials and methods. A total of 35 patients with COPD aged 60–74 years were examined. All the patients were divided into two groups: the main group (18 people) who received breathing exercises with PEEP, and the control group (17 people) who received simulated exercises. The cardiovascular system state was assessed. The examinations were performed in the initial state (before training), immediately after, one month later, and three months after the training course. Results. The cardiovascular system state improved as a result of breathing exercises with PEEP in older patients with COPD. At the same time, the duration of the breathing exercises with PEEP action was short; the effect of their use was not preserved in a month. Relationships between shifts in SpO2 and cardiac output, as well as between shifts in SpO2 and peripheral vascular resistance immediately after the use of breathing exercises with PEEP in older patients with COPD have been established. A more significant and prolonged effect of breathing exercises with PEEP on the cardiovascular system functional state was observed in older COPD patients with more severe symptoms of the disease. Conclusions. The increase in cardiovascular performance was influenced by breathing exercises with PEEP in older COPD patients due to the improved lung oxygenation capacity. The effect of breathing exercises with PEEP remained within a month after the training course and was more stable and longer in patients with severe clinical symptoms. Older COPD patients are advised to repeat the courses of breathing exercises with PEEP every month.